Sensorineural Hearing Loss and Celiac Disease: A Coincidental Finding - Umberto Volta; Gian Gaetano Ferri; Roberto De Giorgio; Angela Fabbri; Claudia Parisi; Laura Sciajno; Alessandra Castellari; Erica Fiorini; Maria Piscaglia; Giovanni Barbara; Alessandro Granito; Antonio Pirodda (Canadian Journal of Gastroenterology)
BACKGROUND: Celiac disease (CD) can be associated with a variety of extraintestinal manifestations, including neurological diseases. A new neurological correlation has been found between CD and sensorineural hearing loss (SNHL).